A CCAAT-binding factor, SlNFYA10, negatively regulates ascorbate accumulation by modulating the d-mannose/l-galactose pathway in tomato. (1st December 2020) - Chen, Weifang; Hu, Tixu; Ye, Jie; Wang, Bing; Liu, Genzhong; Wang, Ying; Yuan, Lei; Li, Jiaming; Li, Fangman; Ye, Zhibiao; Zhang, Yuyang
Abstract: Ascorbic acid (AsA), an important antioxidant and growth regulator, and it is essential for plant development and human health. Specifically, humans have to acquire AsA from dietary sources due to their inability to synthesize it. The AsA biosynthesis pathway in plants has been elucidated, but its regulatory mechanism remains largely unknown. In this report, we biochemically identified a CCAAT-box transcription factor (SlNFYA10) that can bind to the promoter of SlGME1, which encodes GDP-Man-3', 5'-epimerase, a pivotal enzyme in the d -mannose/l -galactose pathway. Importantly, SlNFYA10 simultaneously binds to the promoter of SlGGP1, a downstream gene of SlGME1 in the d -mannose/l -galactose pathway. Binding assays in yeast and functional analyses in plants have confirmed that SlNFYA10 exerts a negative effect on the expression of both SlGME1 and SlGGP1 . Transgenic tomato lines overexpressing SlNFYA10 show decreased levels of SlGME1 and SlGGP1 abundance and AsA concentration in their leaves and fruits, accompanied by enhanced sensitivity to oxidative stress. Overall, SlNFYA10 is the first CCAAT-binding factor identified to date to negatively regulate the AsA biosynthetic pathway at multiple sites and modulate plant responses to oxidative stress.